Integrated transcriptomic and proteomic analyses of P. falciparum gametocytes: molecular insight into sex-specific processes and translational repression - Lasonder, Edwin; Rijpma, Sanna R.; van Schaijk, Ben C. L.; Hoeijmakers, Wieteke A. M.; Kensche, Philip R.; Gresnigt, Mark S.; Italiaander, Annet; Vos, Martijn W.; Woestenenk, Rob; Bousema, Teun; Mair, Gunnar R.; Khan, Shahid M.; et al. (Nucleic acids research, 2016)
Abstract. Sexual differentiation of malaria parasites into gametocytes in the vertebrate host and subsequent gamete fertilization in mosquitoes is essential fo